INTERACTIONS OF THE eNOS AND ACE GENES AND CIGARETTE SMOKING IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE: The eNOS and ACE genes and cigarette smoking in COPD - Stankovic, Marija; Djordjevic, Valentina; Tomovic, Andrija; Nagorni-Obradovic, Ljudmila; Petrovic-Stanojevic, Natasa; Kovac, Mirjana; Radojkovic, Dragica (Journal of Medical Biochemistry, 2022)
Background: Chronic obstructive pulmonary disease (COPD) is a complex disorder with unexplained heritability. Interactions of genetic and environmental factors are thought to be crucial in COPD. So, we aim to examine interactions of the endothelial nitric oxide synthase (eNOS) and angiotensine converting enzyme (ACE) genes and cigarette smoking in COPD. Methods: The eNOS G894T and ACE ID variants were analyzed in 322 COPD patients and controls from Serbia. The effect of the variants on COPD was assessed by logistic regression. Interactions between eNOS, ACE and cigarette smoking in COPD were evaluated using a case-control model. Interaction between the genes was analyzed in silico. Results: No effect of the eNOS G894T and ACE ID variants on COPD was found in our study. Gene-gene interaction between the eNOS TT and ACE D was identified (p=0.033) in COPD. The interaction is realized within the complex network of biochemical pathways. Gene-environment interactions between the eNOS T and cigarette smoking (p=0.013), and the ACE II and cigarette smoking (p=0.009) were detected in COPD in our study. Conclusions: This is the first research to reveal interactions of the eNOS and ACE genes and cigarette smoking in COPD progressing our understanding of COPD heritability contributing to the development of appropriate treatments.